2022
DOI: 10.5409/wjcp.v11.i4.330
|View full text |Cite
|
Sign up to set email alerts
|

Effects of adherence to the Mediterranean diet in children and adolescents with irritable bowel syndrome

Abstract: BACKGROUND Irritable bowel syndrome (IBS) is a highly prevalent gastrointestinal disorder in children and adults, which increased over the past twenty years. The Mediterranean diet is a well-known diet full of antioxidants and anti-inflammatory ingredients. AIM To evaluate the safety, tolerability, and effects of adherence to the Mediterranean diet on disease patterns in children and adolescents with IBS. METHODS This prospective, cross-secti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 38 publications
0
16
0
Order By: Relevance
“…In a two-arm, two-site clinical trial, short-term MD compliance was effective in improving some microvascular physiological properties and quality of life domains, suggesting also that further improvement could be obtained in individuals with long-term MD compliance [94]. In a prospective, cross-sectional, case-control study conducted on 100 children and adolescents with irritable bowel syndrome (IBS), MD adherence was associated with considerable improvement in IBS scores, including participants' quality of life [95]. In a 12-weeks, parallel-group, open-label, randomized, controlled trial conducted on 72 young males (18-25 years), an MD intervention resulted in considerable reductions in depression scores and increases in quality-of-life scores compared with befriending [96].…”
Section: Discussionmentioning
confidence: 99%
“…In a two-arm, two-site clinical trial, short-term MD compliance was effective in improving some microvascular physiological properties and quality of life domains, suggesting also that further improvement could be obtained in individuals with long-term MD compliance [94]. In a prospective, cross-sectional, case-control study conducted on 100 children and adolescents with irritable bowel syndrome (IBS), MD adherence was associated with considerable improvement in IBS scores, including participants' quality of life [95]. In a 12-weeks, parallel-group, open-label, randomized, controlled trial conducted on 72 young males (18-25 years), an MD intervention resulted in considerable reductions in depression scores and increases in quality-of-life scores compared with befriending [96].…”
Section: Discussionmentioning
confidence: 99%
“…[73] AI-Bilagi et al reported similar results, the compliance with MD for 6 months remarkably elevated symptoms in children and adolescent patients with IBS. [74] This may be because of the high percentage of unsaturated fatty acids and phenolic compounds, and strict calorie limitation, which benefits the defense against bacterial and fungal infections, and chronic inflammation. Based on our previous discussion between dietary nutrients and mycobiome-increased intake of high-quality protein, fresh plant foods, and unsaturated fatty acid-MD may be the most ideal pattern for patients with FGIDs.…”
Section: Recommended Diets For Patients With Fgidsmentioning
confidence: 99%
“…Furthermore, this dietary pattern often contemplates foods rich in polyunsaturated fatty acids (PUFA), nitrate/nitrite/NO and polyphenolic agents, which have a vasodilatory effect, anti-inflammatory, immunomodulating, antioxidant properties and improve tissue micro-regulation. [ 48 , 61 , 62 ]. The MD is also effective in increasing gut-beneficial bacterial species, thus creating an anti-inflammatory environment [ 62 ].…”
Section: The Mediterranean Diet and Functional Gastrointestinal Disor...mentioning
confidence: 99%
“…The most promising was the one by Al-Biltagi et al, who aimed to assess the tolerance, security and efficacy of the MD in children and adolescents with IBS. In their 100-people study, half of the patients received a six-month MD with good adherence, while the other half continued their regular diet [ 61 ]. The MD was well-tolerated by the patients, and was free from adverse reactions, as well as proving effective in reducing all IBS scores (IBS-symptoms-severity-score questionnaire, IBS-quality-of-life questionnaire) [ 61 ].…”
Section: The Mediterranean Diet and Functional Gastrointestinal Disor...mentioning
confidence: 99%
See 1 more Smart Citation